MOVEMENT IS THE MAIN FACTOR OF A HEALTHY LIFESTYLE - Gafurov Abdushokir Makhmudovich (International Journal of Innovations in Engineering Research and Technology, 2022)
Each of the 600 muscles in the human body is a special helper of the heart: When the muscles contract, the blood in the small blood vessels in them passes to the large veins and is poured into the heart. So, movement first has a positive effect on the movement of blood in the heart and veins; secondly, as a result of regular movement of the body muscles and heart muscle, their fibers become thicker and the force of contraction increases.